2017
DOI: 10.1101/181909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hemimetabolous genomes reveal molecular basis of termite eusociality

Abstract: Around 150 million years ago, eusocial termites evolved from within the cockroaches, 50 million years before eusocial Hymenoptera, such as bees and ants, appeared. Here, we report the first, 2GB genome of a cockroach, Blattella germanica, and the 1.3GB genome of the drywood termite, Cryptotermes secundus. We show evolutionary signatures of termite eusociality by comparing the genomes and transcriptomes of three termites and the cockroach against the background of 16 other eusocial and non-eusocial insects. Dra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…Especially, expression levels of three genes involved in ecdysone synthesis (shadow, shade, and spookier) were highly upregulated. This was consistent with the previous reports, which showed that ecdysone receptor signaling activity was important for presoldier and soldier formations in Z. nevadensis (Masuoka & Maekawa, 2016), and that the caste-specific expressions of ecdysone synthesis genes were broadly observed among three termite species including Z. nevadensis (Harrison et al, 2018).…”
Section: The Potential Molecular Mechanisms Of Soldier Differentiationsupporting
confidence: 93%
“…Especially, expression levels of three genes involved in ecdysone synthesis (shadow, shade, and spookier) were highly upregulated. This was consistent with the previous reports, which showed that ecdysone receptor signaling activity was important for presoldier and soldier formations in Z. nevadensis (Masuoka & Maekawa, 2016), and that the caste-specific expressions of ecdysone synthesis genes were broadly observed among three termite species including Z. nevadensis (Harrison et al, 2018).…”
Section: The Potential Molecular Mechanisms Of Soldier Differentiationsupporting
confidence: 93%
“…35 To date, at least one CYP4G gene has been found in all insects with sequenced genomes. The B. germanica genome contains only one CYP4G gene, 33 and we have found that it plays a role in hydrocarbon production. Likewise, Acyrthosiphon pisum CYP4G51 and Apis mellifera CYP4G11, the only CYP4G member in each species, have also been shown to be involved in hydrocarbon biosynthesis.…”
Section: Discussionmentioning
confidence: 91%
“…31 However, two CYP4G subfamily genes, CYP4G16 and CYP4G17, have been reported to be positively associated with cuticular resistance via catalyzing the production of CHCs in A. gambiae. 9,32 The only CYP4G member in B. germanica, CYP4G19, 33 was reported to be overexpressed in a pyrethroid-resistant strain, 34 but no role in insecticide resistance has been attributed to CYP4G19. Several CYP4G genes have been functionally characterized to be involved in the final decarbonylation step of hydrocarbon biosynthesis by baculovirus expression system 9,[35][36][37] or RNAi-based functional studies.…”
Section: Introductionmentioning
confidence: 99%
“…A second large repertoire of 3 receptors implicated in insect gustation is the Ionotropic Receptor (IR) family, which are ligand-gated ion channels that have derived from synaptic ionotropic glutamate receptors (iGluRs) [14][15][16][17] . Unlike iGluRs, IRs display enormous diversification both in the size of the repertoire across insects (ranging from tens to several hundreds 15,16,18 ), and in their protein sequences (with as little as 10% amino acid identity between pairs of receptors). IRs have been best-characterised in the vinegar fly, Drosophila melanogaster, which possesses 60 intact Ir genes.…”
mentioning
confidence: 99%